Affordability of Fertility Treatments and Multiple Births in the United States. Issue 5 (1st August 2017) - Kulkarni, Aniket D.; Adashi, Eli Y.; Jamieson, Denise J.; Crawford, Sara B.; Sunderam, Saswati; Kissin, Dmitry M.
Abstract: Background: Affordability plays an important role in the utilisation of in vitro fertilisation (IVF) and non‐IVF fertility treatments. Fertility treatments are associated with increased risk of multiple births. The objective of this study was to investigate the association between the affordability of fertility treatments across US states and the percentage of multiple births due to natural conception, non‐IVF treatments, and IVF, and the association between these percentages and state‐specific multiple birth rates. Methods: State‐specific per capita disposable personal income and state‐specific infertility insurance mandates were used as measures of affordability. Maternal age‐adjusted percentages of multiple births due to natural conception, non‐IVF treatments, and IVF were estimated for each state using birth certificate and IVF data. Scatter plots and regression analysis were used to explore associations between state‐level measures of affordability, the percentage of multiple births due to natural conception and fertility treatments, and state‐specific multiple birth rates. Results: In 2013, age‐adjusted contributions of natural conception, non‐IVF fertility treatments, and IVF to multiple births in US were 58.2, 22.8, and 19.0% respectively. States with greater affordability of fertility treatments had higher percentages of multiples due to IVF and lower percentages due to natural conception. Higher percentages of multiples due to IVF and lower percentages due to natural conception were associated with higher state‐specific multiple birth rates. Conclusion: Increasing affordability of fertility treatments may increase state‐specific multiple birth rates. Policies and treatment practices encouraging single‐gestation pregnancies may help reduce multiple births resulting from these treatments.